The Impact of Learning Management Systems (LMS) on Students' Acquisition of Scientific Concepts and Development of Critical Thinking Skills at Qatari Schools - Kan’an, Ashraf; Alzoabi, Talal Abdullah; Aldulaimi, Mohammed Matar (Dirasat: Educational Sciences, 2020)
The study aims to investigate the effect of using Learning Management Systems (LMS) in teaching the subject of transfer in humans on the acquisition of scientific concepts and critical thinking skills by students of the eleventh grade in Qatari schools. To achieve the aim of the study, the researchers prepared a teacher's guide to learning management system, a test of concept acquisition, and a test of critical thinking skills. A quasi-experimental approach was used, and the study was applied to students of the eleventh grade at Nasser bin Abdullah Al-Attiyah Independent Secondary School for Boys in the State of Qatar. The study sample consisted of (88) students, who were chosen in an intentional method, and were divided into two groups: an experimental group consisting of (50) students, which was taught using the learning management system, and a control group consisting of (38) students who were taught in a usual method. The results of the study showed a statistically significant effect of using learning management system in improving students' acquisition of scientific concepts and improving critical thinking skills for the eleventh graders. The study recommends adopting a learning management system in the teaching of biology, and investigating the effect of using the system on other variables, such as problem-solving and decision-making skills.